Business Method Patents-International Developments - Agarwal, Prashant (Journal of Commerce and Trade, 2012)
Business Method may be defined as “a method of operating any aspect of business enterprise”. A business method is classified as a process because it is not a physical object like a mechanical invention or chemical composition. Business Method Patents being usually process patent in nature and the same can be interpreted as new and useful process being patented under this kind of patents. A business method patent confers upon its holder a set of exclusive rights with respect to a particular manner in which a business operation can be carried out. A business method patent confers upon its holder a set of exclusive rights with respect to a particular manner in which a business operation can be carried out. It constitutes a special category of patents which are conferred for operating business in an innovative way. Business method patents are most commonly associated with electronic commerce and other computer related supported infrastructures for carrying business operations.